A Prospective Study of Voice, Swallow, and Airway Outcomes Following Tracheostomy for COVID‐19. (28th December 2020) - Rouhani, Maral J.; Clunie, Gemma; Thong, Gerard; Lovell, Lindsay; Roe, Justin; Ashcroft, Margaret; Holroyd, Andrew; Sandhu, Guri; Al Yaghchi, Chadwan
Abstract : Objective: The COVID‐19 pandemic has led to unprecedented demands on healthcare with many requiring intubation. Tracheostomy insertion has often been delayed and the enduring effects of this on voice, swallow, and airway outcomes in COVID‐19 tracheostomy patients are unknown. The aim of this study was to prospectively assess these outcomes in this patient cohort following hospital discharge. Methods: All COVID‐19 patients who had undergone tracheostomy insertion, and were subsequently decannulated, were identified at our institution and followed up 2 months post‐discharge. Patient‐reported (PROMS) and clinician‐reported outcome measures, endoscopic examination, and spirometry were used to assess voice, swallow, and airway outcomes. Results: Forty‐one patients were included in the study with a mean age of 56 years and male:female ratio of 28:13. Average duration of endotracheal intubation was 24 days and 63.4% of tracheostomies were performed at day 21 to 35 of intubation. 53.7% had an abnormal GRBAS score and 30% reported abnormal swallow on EAT‐10 questionnaire. 81.1% had normal endoscopic examination of the larynx, however, positive endoscopic findings correlated with the patient self‐reported VHI‐10 ( P = .036) and EAT‐10 scores ( P = .027). 22.5% had spirometric evidence of fixed upper airway obstruction using the Expiratory‐Disproportion Index (EDI) and Spearman correlation analysis showed a positive trend between abnormal endoscopic findings and EDI scores over 50 ( P < .0001). Conclusion: The preliminary results of this study reveal a high incidence of laryngeal injury among patients who underwent intubation and tracheostomy insertion during the COVID‐19 pandemic. As these patients continue to be followed up, the evolution of these complications will be studied. Level of Evidence: 3 Laryngoscope, 131:E1918–E1925, 2021